Revision of Mistika Mohamedsaid from the great Sunda area, with description of a new genus (Coleoptera: Chrysomelidae: Alticinae) - Mohamed Dawoodi , Mahadimenakbar; Haruo Takizawa , (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
Genus Mistika Mohamedsaid was revised with six new species: Mistika montana, M. sabahcola and M. similis n. spp. from Borneo, M. hamidi and M. minima n. spp. from Sumatra, and M. sugiyamai n. sp. from Malay Peninsula. Also a closely related new genus and species, Balimistika mohamedsaidi gen. et sp. n. was described from Bali Is. These species compose a single group, which falls between subfamilies Alticinae and Galerucinae.